2012
DOI: 10.1002/pchj.10
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement control in reading: Logographic Chinese versus alphabetic scripts

Abstract: Eye tracking is widely used to study the reading process in different languages. Given the unique properties of written Chinese, it is important to identify the similarities and differences in eye-movement controls between readers of Chinese and alphabetic scripts. In this article, we review the data available for comparison in four domains: (a) the perceptual span, (b) parafoveal processing, (c) the basic encoding unit, and (d) computer modeling. Our review indicates that, while some aspects of eye movement c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 102 publications
1
17
1
Order By: Relevance
“…For example, Pollatsek, Lesch, Morris, and Rayner () demonstrated that, parafoveally presented homophonic previews facilitated processing of the target word in FFD, relative to non‐homophonic preview words. In contrast, although remnants of inner voice can still be found in silent reading among Chinese adults (e.g., Yan, Luo, and Inhoff, ), it is commonly accepted that pure parafoveal phonological effects without orthographic similarity during the silent reading of Chinese sentences may not be as effective (see also Tsang and Chen, , for a review): First, homophonic preview effects have been consistently shown only for GD during the silent reading of Chinese sentences (Liu, Inhoff, Ye, and Wu, ; Tsai, Lee, Tzeng, Hung, and Yen, ; Yan et al, ). Arguably, as GD includes refixations, it is usually interpreted as an index for a relatively later duration measure than FFD (Inhoff, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pollatsek, Lesch, Morris, and Rayner () demonstrated that, parafoveally presented homophonic previews facilitated processing of the target word in FFD, relative to non‐homophonic preview words. In contrast, although remnants of inner voice can still be found in silent reading among Chinese adults (e.g., Yan, Luo, and Inhoff, ), it is commonly accepted that pure parafoveal phonological effects without orthographic similarity during the silent reading of Chinese sentences may not be as effective (see also Tsang and Chen, , for a review): First, homophonic preview effects have been consistently shown only for GD during the silent reading of Chinese sentences (Liu, Inhoff, Ye, and Wu, ; Tsai, Lee, Tzeng, Hung, and Yen, ; Yan et al, ). Arguably, as GD includes refixations, it is usually interpreted as an index for a relatively later duration measure than FFD (Inhoff, ).…”
Section: Discussionmentioning
confidence: 99%
“…Chinese is particularly well suited for demonstrating semantic parafoveal processing not only because of its characteristically strong connection between orthography and semantics, as mentioned earlier (see also Hoosain, 1991;Tsang & Chen, 2012, for reviews) but also because of other important factors. For example, most Chinese words are only one or two characters in length, and a Chinese character typically occupies the space of three letters in alphabetic languages (Tsai & McConkie, 2003).…”
Section: Relevant Features Of the Chinese Writing System And Their Immentioning
confidence: 93%
“…As they do so, the acquire information not only from the fixated foveal words but also from the upcoming parafoveal words within the perceptual span (defined as the area from which readers can obtain useful information; see Rayner, 2009 andTsang &Chen, 2012, for reviews). The perceptual span, as demonstrated using the gaze-contingent moving window paradigm, extends 3-4 letters to the left and 14-15 letters to the right of fixation for English readers (McConkie & Rayner, 1975), 1 character to the left and up to 4 characters to the right of fixation for Chinese readers (Inhoff & Liu, 1998;Tsai & McConkie, 1995;Yan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%